The effects of exposure to endocrine-disrupting chemicals in intrauterine life on thyroid function tests during the neonatal period - Özsoylu, Serkan; Güneş, Tamer; Akın, Leyla; Kendirci, Mustafa (Journal of Surgery and Medicine, 2021)
Background/Aim: Animal studies have shown that endocrine-disrupting chemicals can cause transient hypothyroidism. The aim of this study is to investigate the effects of exposure to endocrine disrupting chemicals (polychlorinated biphenyls (PCBs), polybrominated biphenyls (PBBs), bisphenol A (BPA) in plastics) in intrauterine life on thyroid function tests during the neonatal period. Methods: In this observational cohort study, cord blood samples were obtained from all infants at birth to measure endocrine disruptors. Serum bisphenol A, di-(2-ethylhexyl) phthalate, and mono-ethylhexyl phthalate levels were measured by high performance liquid chromatography (HPLC). We excluded newborns whose mothers had thyroid function disorders. Results: The male newborns’ cord bisphenol A concentrations were significantly higher than those of female newborns (1.14 (0.26) ng/ml vs 0.85 (0.25) ng/ml, respectively; P=0.007). When we examined the correlation between the cord blood phthalate values and the maternal and newborn’s thyroid function tests, a negative relationship between mono-ethylhexyl phthalate and newborn thyroid stimulating hormone was detected (r= -0.284, P=0.003). Conclusion: A negative correlation was detected between cord blood mono-ethylhexyl phthalate levels and neonatal thyroid stimulating hormone levels suggesting that phthalate exposure may affect the thyroid function of babies in the prenatal period.